Instituição de acolhimento a crianças e adolescentes em Belo Horizonte: contextualização, regulação e atuação - Rita Ana da Silva Lima (2016)
This project aims to know the history of children and adolescents institutionalized in Brazil and contextualize one host institution for street children and adolescents in Belo Horizonte, Brazil, analyzing how it works for family reintegration according to the technical rules of the National Council for Children and Adolescents (CONANDA). The methodology for this purpose included: literature review about the history of the Brazilian policies for children and adolescents at risk; mapping of host institutions in Belo Horizonte; selection of a representative institution to report its relationship with the public regulatory agencies and its performance to work with family reintegration. According to the requirements of each stage of the research, it was realized technical literature review and simple observation and interview under informed consent. The host institution “Ministério Programa Criança Feliz” (Happy Child Program, MPCF) conducted significant number of reinsertions, exemplified in stories of three families. The MPCF faced numerous technical and financial weaknesses and opted to change the institutional care in the form of shelter for day care after school. Its current goal is the prevention of breaking of family bonds between child or adolescent with their families in their social context, while maintaining its mission and values. This research highlights the need for a better articulation between the institutions and public agencies to improve service.